Cash flow analysis and forecasting : the definitive guide to understanding and using published cash flow data - Jury, Timothy D. H. (John Wiley & Sons, 2012)
This book is the definitive guide to cash flow statement analysis and forecasting. It takes the reader from an introduction about how cash flows move within a business, through to a detailed review of the contents of a cash flow statement. This is followed by detailed guidance on how to restate cash flows into a template format. The book shows how to use the template to analyse the data from start up, growth, mature and declining companies, and those using US GAAP and IAS reporting. The book includes real world examples from such companies as Black and Decker (US), Fiat (Italy) and Tesco (UK.